Silencing β1,2-xylosyltransferase in Transgenic Tomato Fruits Reveals xylose as Constitutive Component of Ige-Binding Epitopes. - Sonnewald, Uwe; Kogel, Karl-Heinz; Pabst, Martin; Paulus, Kathrin; Altmann, Friedrich; Mahler, Vera (Frontiers in Plant Science, 2011)
Complex plant N-glycans containing β1,2-xylose and core α1,3-fucose are regarded as the major class of the so-called "carbohydrate cross-reactive determinants" reactive with IgE antibodies in sera of many allergic patients, but their clinical relevance is still under debate. Plant glycosyltransferases, β1,2-xylosyltransferase (XylT), and core α1,3-fucosyltransferase (FucT) are responsible for the transfer of β1,2-linked xylose and core α1,3-linked fucose residues to N-glycans of glycoproteins, respectively. To test the clinical relevance of β1,2-xylose-containing epitopes, expression of the tomato β1,2-xylosyltransferase was down-regulated by RNA interference (RNAi) in transgenic plants. Fruits harvested from these transgenic plants were analyzed for accumulation of XylT mRNA, abundance of β1,2-xylose epitopes and their allergenic potential. Based on quantitative real-time PCR analysis XylT mRNA levels were reduced up to 10-fold in independent transgenic lines as compared to untransformed control, whereas no xylosylated N-glycans could be revealed by MS analysis. Immunoblotting using anti-xylose-specific IgG antibodies revealed a strong reduction of β1,2-xylose-containing epitopes. Incubating protein extracts from untransformed controls and XylT_RNAi plants with sera from tomato allergic patients showed a patient-specific reduction in IgE-binding, indicating a reduced allergenic potential of XylT_RNAi tomato fruits, in vitro. To elucidate the clinical relevance of β1,2-xylose-containing complex N-glycans skin prick tests were performed demonstrating a reduced responsiveness of tomato allergic patients, in vivo. This study provides strong evidence for the clinical relevance of β1,2-xylose-containing epitopes in vivo.
Keywords: beta 1; 2-xylosyltransferase; RNA interference; tomato allergy; N-glycosylation; CCDs